Takagi-sugeno fuzzy gains scheduled PI controller for enhancement of power system stability - Hassan, L.H.; Moghavvemi, M.; Mohamed, H.A.F. (Science Publications, 2010)
Problem statement: Power system oscillations affect system stability and may lead to failure if not properly controlled. Approach: A Takagi-Sugeno Fuzzy Gains Scheduled Proportional and Integral (FGPI) controller was proposed for a Thyristor Controlled Series Capacitor (TCSC)-based stabilizer to enhance the power system stability. Linguistic rules and fuzzy inference mechanism are utilized to tune the controller parameters on-line in different operating states. The proposed controller was applied to a single machine infinite bus system represented by the Phillips-Heffron generator model. Simulation studies have been carried out using MATLAB Fuzzy Logic toolbox. Simulated Annealing-based Power System Stabilizer (SAPSS) and Simulated Annealing-based TCSC Stabilizer (SACSC) approaches were also simulated in this study and their results were compared with proposed controller. Results: The simulation results demonstrated that the proposed control scheme performs well and strongly control the power system under different loading conditions, disturbances and system parameter variations. Conclusion: The proposed controller is robust and more suitable for damping of low frequency oscillation and more effective in improving dynamic stability and voltage profile than the two other approaches. © 2010 Science Publications.